Hubungan Konstruksi dan Jarak Sumber Pencemar terhadap Kualitas dan Status Mutu Air Sumur Gali di Desa Banyuajuh, Kamal - Nuril Fitriyah; Widya Nilandita; Sarita Oktorina (Universitas Batanghari Jambi, 2022)
The background of this research is that most of the rural communities, one of which is Banyuajuh Village, Kamal, Bangkalan, utilizes clean water sources from ground water. However, people do not pay attention to how to build wells with the characteristics and distance from the pollutant source correctly. Therefore, this study aims to determine the construction and distance of the well from the pollutant source, the quality parameters of Temperature, pH, Turbidity, TDS, CaCOs, and Total Coliform based on the quality standard of the Minister of Health of the Republic of Indonesia No. 32 of 2017 and the water quality index at the research site using the Pollution Index (IP) method by conducting a preliminary survey then followed by sampling 2 times at 3 sampling locations referring to SNI 6989.58 2008 for sample testing. After that, an analysis was carried out using the Pollution Index (IP) method for determining the status of groundwater quality which will be presented in a qualitative descriptive form. Based on the results of the study obtained the result that there was construction and the distance between the well and the pollutant source at location A for the floor of the well, the diameter of the well covering the well, the hoist and the distance between the well and the pollutant source were not qualify. At location B for all constructions and the distance from the well to the pollutant source does not meet the requirements. At location C, the height of the well lip, the diameter of the well, the cover of the well, the hoist and the distance between the well and the pollutant source, do not meet the requirements. The groundwater quality parameters (wells) exceed the quality standards in the form of temperature at locations A1: 29°C, A2 30°C and total coliform parameters at locations A1 21,100 CFU/100m, A2 22,600 CFU/100m, B1: 24,000 CFU/100m, B2 : 24,500 CFU/100m, C1: 180, C2: 840 CFU/100m Meanwhile, the water quality index based on the IP method is moderately polluted at location A (with Plj 8.28) and location B (with Plj 8.16) and lightly polluted at location C (with Plj 4.88).